Ciclo de desenvolvimento de projeto baseado em desempenho do material: dos processos digitalmente mediados à fabricação local - Omena, Thiago Henrique (Universidade de São Paulo, 2019)
Considering the need to adapt, for local and non-specialized hand labor, the design development cycle based on material performance, this thesis aims to compare design methods of C 2 curvature morphologies, through form-making, algorithmic and form-finding models, and thus to evaluate their structural performances; to produce a polymeric composite material with natural fiber and; at last, to generalize a design development cycle that encompasses fabrication with composite materials of morphologies originated by digital design. In this sense, the study relied on a design driven research approach, known as design research, in addition to an exploratory, application, descriptive and experimental methodology. In this way, it was observed that, the simulated performance-based models presented lower results in the maximum deformation and elastic energy of deformation that resulted in optimized structures that requires less material to be produced. This allowed to conclude, that the design development cycle proposed by this research is capable of enabling non-conventional forms generated by digital design and fabricated with polymer composites.